TANGGUNG JAWAB PENGANGKUT ATAS TENGGELAMNYA KAPAL (ANALISIS PUTUSAN MAHKAMAH PELAYARAN NOMOR HK.212/01/I/MP.2020) - Nabila Sesha Abdillah; Siti Nurbaiti (Reformasi Hukum Trisakti, 2023)
In Indonesian waterways, ferries are a kind of transportion used to move both people and cargo. However, as was the case with the sinking of the KMP Saluang, transportation will not always go as planned. The problems to be discussed: how is the carrier should be held accountable for the sinking of the KMP Saluang under the terms of Law No. 17 of 2008 concerning Shipping and how is the carrier accountable for compensating the owner of the goods for the sinking of the KMP Saluang. This research is descriptive in character, normative, and uses both secondary and primary data. It also employs qualitative analysis and deductive conclusion-drawing. The study's findings, analysis, and recommendations show that, in accordance with Article 41 paragraph (1) sub-b of the Shipping Law, the carrier should be held accountable for the destruction of the goods sent by the sender of the goods and temporarily revoke the Seaman Expertise Certificate for a period one month. The Presumption of Liability system should be used by the carrier's responsibility system to provide recompense to the owner of the products, although in this instance the proof was not carried out by the carrier.